Container Misdeclaration Practices and Their Impact on Ship Safety: A Qualitative Study in the Shipping Industry: Praktik Misdeklarasi Kontainer dan Dampaknya terhadap Keselamatan Kapal: Studi Kualitatif pada Industri Pelayaran - Ratna Kurnia Dewi; Atria Maharani (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
This study aims to describe the phenomenon of misdeclaring container weight and contents by shippers and freight forwarders and its impact on ship operational safety. This problem arises from the practice of falsifying weights, packaging that does not comply with international standards, and concealing hazardous cargo, which has contributed to the increase in container ship accidents over the past decade. A qualitative approach was used to understand the experiences and perceptions of shipowners, seafarers, and relevant authorities. Data were collected through in-depth interviews, document studies of container ship accidents, and analysis of reports from international maritime agencies. Thematic analysis techniques were used to identify patterns of misdeclaration practices, causal factors, and the risks they pose to ship stability and crew safety. The results show that misdeclaring container weights causes structural imbalances in cargo, increases pressure on container stacks, and triggers containers to fall overboard. Meanwhile, misdeclaring hazardous cargo has the potential to cause chemical reactions, fires, explosions, and the release of toxic gases when ships are in open waters. The findings also reveal weak oversight of the implementation of the verified gross weight policy and the limitations of international customs inspections, which still rely on shipper declarations. In conclusion, container misdeclaration is a serious threat to the shipping industry and requires strengthening regulations, improving seafarers' competency, and establishing independent verification mechanisms to ensure the safety and security of the maritime logistics chain.